Resource at risk Philippine coral reefs. - Bookmark (Quezon City Bookmark Video and Moving Images, 1998)
This video documentary tackles the vital issue of coral reef destruction in the Philippines. Coral reefs are one of our most precious resources. They are to the sea what forest are to the land. One square kilometer of healthy reef can produce up to 30 metric tons of fish a year. More than 50% of the Filipino people depend on the sea for their main source of protein.
But as this documentary makes clear, the pHilippines is fast running out of healthy reefs. Nearly all of our reefs have been damaged by destructive fishing methods like dynamite fishing, and catches nationwide are dropping sharply. As reefs die, in a few years, the nation will no longer to be able to feed itself. Millions of Filipinos could starve.
There remains hope. This documentary also shows the ways by which we can save our reefs. But we have to start now. Ultimately, protecting our reefs is everyone's concern. (taken from the case)
Creative Director/Writer: Raul Rodrigo; Post Production Director: Joey Conti; Production Manager: Stella Chiu; Consultant: Lory Tan
Keywords: Coral Reefs -- Philippines